Relating millimeter‐scale turbulence to meter‐scale subtidal erosion and accretion across the fringe of a coastal mangrove forest. Issue 3 (19th January 2021) - Norris, Benjamin K.; Mullarney, Julia C.; Bryan, Karin R.; Henderson, Stephen M.
Abstract: Within a wave‐exposed mangrove forest, novel field observations are presented, comparing millimeter‐scale turbulent water velocity fluctuations with contemporaneous subtidal bed elevation changes. High‐resolution velocity and bed level measurements were collected from the unvegetated mudflat, at the mangrove forest fringe, and within the forest interior over multiple tidal cycles (flood–ebb) during a 2‐week period. Measurements demonstrated that the spatial variability in vegetation density is a control on sediment transport at sub‐meter scales. Scour around single and dense clusters of pneumatophores was predicted by a standard hydraulic engineering equation for wave‐induced scour around regular cylinders, when the cylinder diameter in the equations was replaced with the representative diameter of the dense pneumatophore clusters. Waves were dissipated as they propagated into the forest, but dissipation at infragravity periods (> 30 s) was observed to be less than dissipation at shorter periods (< 30 s), consistent with the predictions of a simple model. Cross‐wavelet analysis revealed that infragravity‐frequency fluctuations in the bed level were occasionally coherent with velocity, possibly indicating scour upstream of dense pneumatophore patches when infragravity waves reinforced tidal currents. Consequently, infragravity waves were a likely driver of sediment transport within the mangrove forest. Near‐bed turbulent kinetic energy, estimated from the turbulent dissipation rate, was also correlated with bed level changes. Specifically, within the mangrove forest and over the unvegetated mudflat, high‐energy events were associated with erosion or near‐zero bed level change, whereas low‐energy events were associated with accretion. In contrast, no single relationship between bed level changes and mean current velocity was applicable across both vegetated and unvegetated regions. These observations support the theory that sediment mobilization scales with turbulent energy, rather than mean velocity, a distinction that becomes important when vegetation controls the development of turbulence. Abstract : Infragravity waves are likely driver of sediment transport in mangroves across large (forest‐wide) scales. Mangrove roots generate near‐bed turbulence through drag forces, which affects sediment transport over small (< 1 m 2 ) scales.